IMPLEMENTATION OF THE BLENDED LEARNING MODEL IN SOIL MECHANICS PRACTICE COURSES IN BUILDING ENGINEERING EDUCATION STUDY PROGRAM STATE UNIVERSITY OF JAKARTA - Adilah Nuril Hidayah Septiari; Tuti Iriani; Daryati (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This study aims to describe the implementation of blended learning in the Soil Mechanics Practice course in the S1 Building Engineering Education study program at UNJ. The implementation of blended learning is divided into Online and Offline learning where Online learning is carried out through Google Classroom and Zoom and Offline learning is carried out at the Soil Mechanics Laboratory. This study uses a quantitative approach with a survey method. Respondents were 76 undergraduate students of Building Engineering Education who took the Soil Mechanics Practice course in the Even Semester of the 2021/2022 Academic Year. Collecting data using a questionnaire. The results of this study indicate that the application of blended learning received many positive responses from students who stated that learning was fun and increased creativity, activeness by 53.95% agreed, increased interest, readiness and awareness of student learning by 52.63% strongly agreed, but its application made students to spend more money and effort by 38.16% agreed. However, there was an increase in understanding of the material and practical skills by 42.11% agreed. Thus, it can be concluded that the application of blended learning for the Mechanical Engineering Practice course has a positive impact where lecturers and students are actively involved in learning activities both online and face to face.